Development of a deformation quench partitioning process - Akela, Arbind Kumar; Swamy, K M Sampath; Bhasha, M Gafoor; Kumar, D Satish; Balachandran, G (Sadhana (Bangalore), 2023)
A TRIP assisted 0.22 %C steel with 2.3%Mn, 1.5 %Si, 0.05 % Nb and 0.035%Ti (wt. %), was subjected to a novel deformation quench partitioning treatment in a Gleeble thermomechanical simulator, which resulted in a homogeneously dispersed soft ferrite in tempered martensitic microstructure that gave 1470 MPa tensile strength with 13.5% elongation. The processing involves an initial 10% warm deformation followed by quenching to room temperature. The quenched steel was subject to 5% cold stretching followed by partitioning at 400°C. The processed steel, was bench marked with two types of the conventional quench partitioning heat treatments on the same steel. The steel was quenched to room temperature from full austenitization at 900°C and from an intercritical temperature of 770°C, followed by partitioning at 400°C. The fully austenitized quench partitioned steel gave 1499 MPa tensile strength with 8.5% elongation, while the intercritical ausatenitized quench partitioned steel gave 990 MPa tensile strength with 16.1% elongation. The structure property analysis to achieve the high properties is brought out.